AXIOLOGICAL ASPECTS OF TERMINOLOGICAL SYSTEM IN LINGUISTICS (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of axiological aspects of the terminological system in linguistics. In particular, the axiological aspects of the interior design terminology of the Uzbek and English languages were studied based on the analysis of phrases and idioms. It also provides information about the peculiarities of the semantic features of the terminology, taking into account the anthropocentric direction of modern terminology.During the research of the article, a study of the terminological system was carried out from a linguistic point of view: the subject of the article is the semantic and axiological features of terms related to the field of interior design, the goal is to determine the most effective and unique ways of using terms in the field of interior design. It is emphasized that all definitions of the term refer to general characteristics, i.e. special, scientific, professional use. Terms are lexical units of a special-purpose language that express a general, concrete or abstract concept of the theory of a certain special field of knowledge or activity and the correspondence of the term to entry into a certain terminological system; the presence of a special definition; tone and clarity of the lexical item; lack of expression; stylistic ambiguity; it is mentioned that it must have the property of objectivity. The article is based on the scientific views of world and domestic linguists for scientific analysis.